Carbonate biomineralization and heavy metal remediation by calcifying fungi isolated from karstic caves - Dhami, N.; Quirin, M.; Mukherjee, Abhijit (Elsevier BV, 2017)
© 2017 Elsevier B.V.Microbially induced calcium carbonate precipitation (MICP) is a potential technology for creation of durable calcitic minerals. In the current study, we for the first time explored the potential of calcifying ureolytic fungi isolated from Moondyne cave of Western Australia for their biomineralization, metal and radionuclide remediation potential. Two ureolytic isolates Aspergillus sp. UF3 and Fusarium oxysporum UF8 showed significant production of calcite along with co-precipitation of heavy metal Lead and radionuclide Strontium as carbonates. Carbonic anhydrase production in synergism with urease is also reported. Micrographic results demonstrated association of fungal mycelium with biominerals. The biominerals precipitated by calcifying fungi were found to be calcite, vaterite, aragonite along with carbonates and hydroxides of Lead and Strontium. Effective biomineralization with calcium oxalate, a cheap calcium source is also reported. The results of current study suggest that ureolytic fungi from karstic environments bear immense potential for biomineralization, bioremediation and biorecovery of important metals.